Vico, a imaginação da imaginação - Tucci, Daniel Eid (2015)
This dissertation aims to examine the role of imagination in the work New Science of the Neapolitan philosopher Giambattista Vico (1668-1744). The focus of the research is to present the imagination as a concept of unity of knowledge and function of knowledge. For this purpose the dissertation begins with the image title page analysis present in the Scienza Nuova of 1744. This analysis will explore the design, trends and influences that led to the drafting of the image on the title page. An explanation of key concepts relevant follows for interpretation of the viquian opus, decoded from the hieroglyphs present on the title page. After showing the inventiveness of Vico to apply his imagination theory in his own work to achieve the reader, the research seeks to deepen the imagination of the theme as sensorial knowledge of the first people, the poetic wisdom, universal fantastic, the operation of the poetic mind and its requirements as a viquian topical and common sense. This intent aims to understand the contemporary attitude of Vico in his time, his conflicts against divergent school of thought and his concern for the future of humanity